Genome mining reveals high incidence of putative lipopeptide biosynthesis NRPS/PKS clusters containing fatty acyl-AMP ligase genes in biofilm-forming cyanobacteria - Galica, Tomáš; Hrouzek, Pavel; Mareš, Jan (Journal of phycology, 2017)
Cyanobacterial lipopeptides have antimicrobial and antifungal bioactivities with potential for use in pharmaceutical research. However, due to their hemolytic activity and cytotoxic effects on human cells, they may pose a health issue if produced in substantial amounts in the environment. In bacteria, lipopeptides can be synthesized via several well-evidenced mechanisms. In one of them, fatty acyl-AMP ligase (FAAL) initiates biosynthesis by activation of a fatty acyl residue. We have performed a bioinformatic survey of the cyanobacterial genomic information available in the public databases for the presence of FAAL-containing non-ribosomal peptide synthetase/polyketide synthetase (NRPS/PKS) biosynthetic clusters, as a genetic basis for lipopeptide biosynthesis. We have identified 79 FAAL genes associated with various NRPS/PKS clusters in 16% of 376 cyanobacterial genomic assemblies available, suggesting that FAAL is frequently incorporated in NRPS/PKS biosynthetases. FAAL was present either as a stand-alone protein or fused either to NRPS or PKS. Such clusters were more frequent in derived phylogenetic lineages with larger genome sizes, which is consistent with the general pattern of NRPS/PKS pathways distribution. The putative lipopeptide clusters were more frequently found in genomes of cyanobacteria that live attached to surfaces and are capable of forming microbial biofilms. While lipopeptides are known in other bacterial groups to play a role in biofilm formation, motility, and colony expansion, their functions in cyanobacterial biofilms need to be tested experimentally. According to our data, benthic and terrestrial cyanobacteria should be the focus of a search for novel candidates for lipopeptide drug synthesis and the monitoring of toxic lipopeptide production.
Keywords: microbial biofilm; genom bakteriální; Bacterial Proteins; cyanobacteria; genome mining; sinice; lipopeptides; fatty-acyl AMP ligase; polyketidsynthasy; Computational Biology; Genome, Bacterial; peptidsynthasy; Cyanobacteria; non-ribosomal peptide synthesis; Peptide Synthases; Polyketide Synthases; bakteriální proteiny; výpočetní biologie